Two new species of Willowsia from New Caledonia (Collembola: Entomobryidae) - Zhang, Feng; Bedos, Anne; Deharveng, Louis (Zootaxa, 2014)
The genus Willowsia is reported for the first time from New Caledonia. Two new species, W. neocaledonica sp. nov. and W. nigra sp. nov., are described based on material deposited at the Muséum National d’Histoire Naturelle, Paris. The new species can be distinguished from other members of the genus by coloration and characters of the dorsal chaetotaxy of the head and terga.